Penetrating Facial Trauma in Children due to a Fishing Spear or Screwdriver - Altun, Serdar; Cetinbas, Ahmet; Okur, M. Ihsan; Bal, Ali; Altun, Aysun Yildiz (Medknow Publications & Media Pvt Ltd, 2016)
[Abstract Not Available]
Çocuklarda zipkin ve tornavida ile meydana gelen penetran yüz yaralanmalari
Keywords: Management; Injury